APLIKASI BEBERAPA EKSTRAK TANAMAN SEBAGAI BAHAN PERANGKAP LALAT BUAH (Bactrocera sp.) - Sri wahyuni; Petrus Deornay (AGRICA, 2018)
Application Some Extracts of plant as Trap Material of Fruit Flies (Bactrocera sp). This study aims to determine: 1) the ability of Pala, Basil and Clove seed extract as a trap material for Bactrocera sp. 2) the best plant extract as a trap material for Bactrocera sp. The extraction activity was carried out at the Laboratory of the Faculty of Agriculture, University of Flores, while the fruit fly trap installation was carried out in Ndengga Rongge Village (± 913 m asl) and Lokoboko (± 698 m asl) in Ende Regency. The study was conducted for 3 months, namely in April - June 2018. Observation variables used included the types of fruit fly found in the field and calculated the level of diversity, abundance and dominance of pests and the capture power of each trap in the type of extraction. There are three types of fruit flies trapped in 3 types of attractants in tomato plantations, namely Bactrocera papaya, Bactrocera umbrosa Fabricius and Bactrocera latifrons Handel. Diversity index of Bactrocera sp. in the research location is still relatively low. The highest abundance is B.papayae with the average value of H '= 1.86 and the lowest is B.latifros (H’= 0,07). There is no dominance of type at research location which indicates that the condition of the ecosystem is still stable. Nutmeg extract is the best attractant trap material as an attractant material in field flies